Percepción del Programa de Reparación Económica de las víctimas y familiares de la violencia política de la provincia Sánchez Carrión. - Juárez Salinas, Yajaira Ekaterina (2019)
This thesis: Perception of the Economic Reparation Program for victims and family members of political violence in the Sánchez Carrión province, includes a period of investigation from May to November 2018. Its purpose is to explain a social event of marked importance for anthropology social, through methods and techniques of social research. Family members and victims of political violence in the province of Sánchez Carrión, beneficiaries of the economic reparations program, for the effects of death and disability, received financial compensation from the State, which ranges from 10,000 new soles and 1,400 new soles.. Reparation that they perceive as unfair because the State did not take into account their history, nor their traumas that remain in their memories, and they think that they want to silence them. They perceive it as unworthy because the economic amount is not worth the life of their relative, nor the material losses, nor does it recognize their human rights. They perceive it as insufficient does not allow to improve their living conditions and does not reward the expenses incurred; The fundamental problem is that they have not been able to access other reparation programs conceived in Law No. 28 592, such as education, health, housing, collective, symbolic and restitution of citizens' rights, as the case may be. Proving with it that the victims and relatives of political violence do not feel repaired; therefore, there can be no talk of reconciliation, between the State and family members and victims of political violence.